Confidentiality and serious harm in genetics - preserving the confidentiality of one patient and preventing harm to relatives. - Lucassen, A; Parker, M (2004)
Genetics can pose special challenges to the principle of confidentiality within the health professional-patient relationship, since genetic information is by its nature both individual and familial. Most professional guidelines allow confidentiality to be broken in rare circumstances, where it will prevent a 'serious', 'imminent' and 'likely' harm. We argue that the types of harms that may result from genetic medicine are particularly diverse. Using clinical examples, we explore ethical issues that arise when balancing individual and family member interests. As genetic testing becomes more, widespread situations will arise where clinicians are faced with a choice between preserving the confidentiality of one patient and preventing harm to another. Professionals need to incorporate the notion of familial implications in their counseling of individuals. Since such dilemmas have been relatively rare in the pre-genetic age, we call for a wider debate on the balance between confidentiality and harm to others.